Front Cover: White Light Generating Molecular Materials: Correlation Between the Amorphous/Crystalline Structure and Nonlinear Optical Properties (ChemPhotoChem 6/2022). Issue 6 (20th June 2022) - Haust, Johannes; Belz, Jürgen; Müller, Marius; Danilo Klee, Benjamin; Link Vasco, Jonathan; Hüppe, Franziska; Rojas Léon, Irán; Christmann, Jan; Beyer, Andreas; Dehnen, Stefanie; Rosemann, Nils W.; Pilgrim, Wolf‐Christian; et al.
Abstract : The Front Cover illustrates the generation of a transmission electron microscopy diffraction pattern from an amorphous adamantane‐type cluster compound and the conversion of infrared laser light into directed white light. Cover design by Elisa Monte. More information can be found in the Research Article by Kerstin Volz and co‐workers .